Pengaruh Pemberian Kunyit Asam terhadap Intensitas Nyeri saat haid pada RemajaTingkat SMA di Pondok Pesantren Darul Hijrah Puteri - Nina Rahmadiliyani; Ainun Qomariah (HB PRESS, 2016)
Dysmenorrhea experienced by woman. The pain felt by every woman is different, it can be mild pain, moderate, or severe that interfere with daily activities and women's health. Turmeric, tamarind is a traditional herb that is believed to be hereditary cope with menstrual pain. This study aims to determine the effect of acid turmeric to the intensity of pain during menstruation in young girls at the senior high school level at Boarding School Darul Hijrah Puteri. This study is a pre-experimental with sampling technique with total sampling are 52 respondents. Measurement of menstrual pain using a pain scale from 0-10 (Comparative Pain Scale) on a checklist. Based on the research before giving turmeric, tamarind majority of respondents experienced mild pain as many as 32 respondents (61.5%), and after giving turmeric acid responde majority do not experience menstrual pain as many as 25 respondents (48.1%). Results Wilcoxon Sign Rank Test, obtain p value= 0.000 < 0.05, so the hypothesis is accepting H1. Which means there are effect giving of turmeric tamarind against the current intensity of menstrual pain in adolescent senior high school level in Boarding School Darul Hijrah Puteri. Keywords : Dysmenorrhea, Turmeric Treatment Acid